2 - The Problem of Unequal Development in African Experiences of Economic Integration - Diouf, Makhtar (Africa Development, 1978)
In this study, the author analyses the experiences of economic co-operation and integration in Africa with a particular stress on the difficulty proceeding from the unequal development of the mem ber states and as a consequence from the unequal profits drawn by these countries which are members of the same economic commu nitty : the more developed countries getting more than the less deve ped ones do. The author, recalling that this fact is inherent in any economic community of the capitalistic type, shows how this pro blem is solved by the conventional theory on international trade which recommends the setting up of a compensation mechanism of finan cial or any other type for the benefit of underprivileged countries. The author, considering the experiences of economic co-opera. tion and integration in Africa, notes that ther first experiences to be carried out : the EAST AFRICAIN COMMUNITY and the CENTRAL AFRICAIN STATES CUSTOMS UNION (U.D.E.A.C.) merely mentio ned in their guiding charters the question of compensation for the benefit of underprivileged countries. As time went by, these economic communities came to realize the importance of the matter and so introduced several compensation mechanisms. In the case of the EAST AFRICAN COMMUNITY, these measures did not succeed in preven ting its split. As for more recent economic communities such as the WEST AFRICAN ECONOMIC COMMUNITY (WAEC) and the ECO NOMIC OMMUNITY OF WEST AFRICAN STATES (.ECOWAS), which have learned from previous experiences, they purposefully provided for compensation mechanisms in their respective charters. However, the efficiency of these compensation mechainsms in terms of rein forcing the unity of these organizations remains to be seen.